Attempts to use statins in cancer therapy: An update - Lucyna Matusewicz; Aleksander Czogalla; Aleksander F Sikorski (Tumor Biology)
Although it could be speculated that almost everything has been said concerning the use of statins in cancer therapy, statins as anticancer drugs have both committed supporters and opponents, for whom the dispute about the legitimacy of statin use in cancer treatment seems never to be clearly resolved; every year more than 300 reports which deepen the knowledge about statins and their influence on cancer cells are published. In this mini-review, we focus on the latest (since 2015) outcomes of cohort studies and meta-analyses indicating statin effectiveness in cancer treatment. We discuss attempts to improve the bioavailability of statins using nanocarriers and review the effectiveness of statins in combined therapies. We also summarise the latest results regarding the development of mechanisms of resistance to statins by cancer cells and, on the other hand, give a few examples where statins could potentially be used to overcome resistance to commonly used chemotherapeutics. Finally, special attention is paid to new reports on the effect of statins on epithelial–mesenchymal transition.